Hubungan Pengetahuan Kader tentang Posyandu terhadap Keaktifan Kader dalam Kegiatan Posyandu di Kelurahan Baleendah Periode September-November 20242024 - Zaelani, Ahmad; Syafriyanti, Willyana; Fidzikri, Nanda Berliana Tania; Ruhayati, Ratih; Aba, Matheus; Mayren, Naency; Manik, Tri Arini Puspa (Innovative: Journal Of Social Science Research, 2025)
The development of the health sector in Indonesia, particularly in healthcare services, is a process that cannot be separated from active community participation. One of the strategies implemented by the government in the health sector is through the Integrated Service Post (Posyandu). Posyandu is a form of Community-Based Health Effort (UKBM) organized by, from, for, and with the community. Each activity within Posyandu is carried out and managed by volunteers (kaders) with technical assistance from healthcare workers. Kaders play a strategic role as the main element in Posyandu operations. Their active participation is a crucial factor in ensuring the sustainability and development of Posyandu so that it continues to function optimally. This study employs a quantitative approach with a cross-sectional research design, where the independent variable analyzed is the knowledge level of kaders about Posyandu, while the dependent variable examined is the level of kader participation in Posyandu activities. The sampling technique used in this study is accidental sampling, with a total of 76 Posyandu kaders as respondents. To analyze the collected data, univariate and bivariate analyses were used, with the chi-square test applied to assess the relationship between variables. The study results indicate that out of the 76 Posyandu kaders surveyed, 42 (55.3%) had good knowledge, 32 (42%) had moderate knowledge, and 10 (13.2%) had poor knowledge about Posyandu. Regarding kader participation, 47 (61.8%) were actively involved in Posyandu activities, while 29 (38.2%) were not active. Bivariate analysis revealed a significant relationship between the level of kader knowledge about Posyandu and their level of participation in Posyandu activities in Baleendah Subdistrict. Therefore, to continuously improve kader knowledge, structured training and coaching sessions should be conducted by local health center (Puskesmas) personnel. Additionally, periodic knowledge refreshment or "refreshing" sessions on relevant Posyandu-related topics are essential to maintain and enhance the quality of services provided.